Análise ergonômica do trabalho: estudo sobre a atividade de camareiras de hotéis em uma cidade do interior do Rio Grande do Norte - Cunha, Ana Karolaynn Souza da (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this research was to perform an ergonomic analysis of the work in hotel maids in the city of Angicos, which is located in the interior of Rio Grande do Norte. Therefore, we chose the two inns (I and II) for an application of the study. In these companies, two functions were addressed for a focal analysis. The research is classified as applied, exploratory, descriptive and with a case study. For data collection, a questionnaire was used to purchase general information and to characterize the site and the research collaborators. For the treatment of the data, the software Ergolândia, version 7.0 was used, which formed the biomechanical values for the ergonomic tools REBA and OWAS. The results showed that, by the REBA method, the employee of the inn I had a severity index of working conditions equal to 7, while the inn II presented the index 5. By the OWAS method, both situations presented index 2. These values, according to the bibliography suggest punctual changes in working conditions. Thus, an intervention action plan was set up using the 5W2H tool to minimize existing ergonomic impacts and thus contribute to the exercise of the function.
Artigo
Keywords: Análise ergonômica do trabalho; Ferramentas; REBA; OWAS; Plano de ações; Ergonomic work analysis; Tools; REBA; OWAS; Action plan; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA